Dyslipidemia, Alcohol Consumption, and Obesity as Main Factors Associated With Poor Control of Urate Levels in Patients Receiving Urate‐Lowering Therapy. Issue 6 (23rd March 2018) - Latourte, Augustin; Bardin, Thomas; Clerson, Pierre; Ea, Hang‐Korng; Flipo, René‐Marc; Richette, Pascal
Abstract : Objective: In real life, in a substantial proportion of gouty patients receiving urate‐lowering therapy (ULT), urate levels are not maintained below the target of 6.0 mg/dl. We aimed to search for factors associated with poor control of serum uric acid (UA) levels in a large population of patients with gout receiving ULT. Methods: This cross‐sectional study involved adults with gout in primary care who were receiving ULT. Demographics, gout history, comorbidities, lifestyle, clinical factors, concomitant treatments, and laboratory data were compared in well‐controlled gout (serum UA ≤6.0 mg/dl) versus poorly controlled gout (serum UA >6.0 mg/dl) on univariate and multivariate analyses. Results: Among the 1, 995 patients receiving ULT, only 445 (22.3%) had reached the target of 6.0 mg/dl serum UA. Such patients had a lower rate of gout flares within the previous year than patients without the target (mean ± SD 1.7 ± 1.4 versus 2.1 ± 1.4; P < 0.0001). The main factors associated with poor serum UA level control in multivariate analysis were low high‐density lipoprotein cholesterol level (adjusted odds ratio [OR] 0.5 [95% confidence interval (95% CI) 0.26–0.96]; P = 0.04), high total cholesterol level (OR 1.83 [95% CI 1.29–2.60]; P = 0.0007), increased waist circumference (OR 1.55 [95% CI 1.11–2.13]; P = 0.008), and alcohol consumption (OR 1.52 [95% CI 1.15–2.00]; P = 0.003). Conclusion: Dyslipidemia, abdominal obesity, and alcohol consumption are the main factors associated with a poor response to ULT. Knowledge of these factors might help physicians identify cases of gout that may be less likely to achieve target urate level.